2018
DOI: 10.1002/ca.23230
|View full text |Cite
|
Sign up to set email alerts
|

Corneal endothelial cell density and cardiovascular mortality

Abstract: Based on embryological commonalities between eye and heart development, a global, country-specific meta-analysis of normal, adult corneal endothelial cell density (ECD) was performed and correlated against mortality rates secondary to diseases affecting cardiac neural crest cell (CNCC)-derived cardiovascular structures. A country-specific survey of ECD was performed by searching PubMed for studies reporting ECD datasets from normal adults. All eligible datasets were assigned a country of origin. Country-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
0
7
0
1
Order By: Relevance
“…Khan et al ( 30 ) also demonstrated a reduction in the corneal ECD and increases in endothelial cell size in patients after acute ischemic stroke. In 2018, Scherer ( 31 ) conducted a global survey and correlative meta-analysis, in which 392 datasets (39,762 eyes) from 267 source studies were assigned to 42 countries. The results of this previous study revealed negative associations between ECD and mortality due to cardiovascular diseases (coronary artery disease and hypertension) on a population-based level ( 31 ).…”
Section: Impact Of Systemic Disorders On Corneal Endothelial Cellsmentioning
confidence: 99%
“…Khan et al ( 30 ) also demonstrated a reduction in the corneal ECD and increases in endothelial cell size in patients after acute ischemic stroke. In 2018, Scherer ( 31 ) conducted a global survey and correlative meta-analysis, in which 392 datasets (39,762 eyes) from 267 source studies were assigned to 42 countries. The results of this previous study revealed negative associations between ECD and mortality due to cardiovascular diseases (coronary artery disease and hypertension) on a population-based level ( 31 ).…”
Section: Impact Of Systemic Disorders On Corneal Endothelial Cellsmentioning
confidence: 99%
“…16 More recently there has again been a downturn. 166 Overall, the average number of approved NCEs per year in the 1970-2005 period was 21.4 "with a statistically significant upward trend . 67 Prudence counsels against immediately concluding from this observation that the transformation of the pharmaceutical industry's dismal state in the nineteenth century to its current nature is attributable to the anti-lemon role of drug regulation.…”
mentioning
confidence: 95%
“…31 Scherer et al reported that in coronary artery disease, CD and mortality are inversely proportional. 32 In our study, when we looked at the correlation of SM findings with arterial oxygen level, FEV1 (%) and FEV1 (L), we found that CD and HEX were also correlated with these three parameters. However, we could not detect such a correlation in CT and CV.…”
mentioning
confidence: 50%